2002
DOI: 10.1002/1439-7633(20020104)3:1<86::aid-cbic86>3.0.co;2-l
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition ofβ-Amyloid Aggregation and Neurotoxicity by Complementary (Antisense) Peptides

Abstract: Complementary peptides are coded for by the nucleotide sequence (read 5'-->3') of the complementary strand of DNA. By reading the sequence of complementary DNA in the 3'-->5' direction, alternative complementary peptides may be derived. We describe the derivation, testing and analysis of six complementary peptides designed against beta-amyloid peptide 1-40 (Abeta, 40). Data is presented to show that one peptide, designated 3' -->5' betaCP1-15, binds specifically to Abeta 1-40, and inhibits both fibrilisation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 27 publications
0
17
0
Order By: Relevance
“…(anti)-idiotypic antibodies [100,101] insulin [102] integrin [103] IFN-g [104] IFN-b [105] IL-1b IL-2 IL-18 [10,11,13,106,107] [108,109] [12] laminin receptor [110] luteinising hormone-releasing hormone [18,111] melanocyte stimulating hormone MHC II/peptide antigens [112] [113] trypsin-modulating oostatic factor [114] myelin basic protein neurokinin A/tachykinin NK1 receptor [33] [ 115] neurophysin II neutrophil chemoattractant nitric oxide synthase [77,116] [117] [118] ovine prolactin bovine P2 protein [119] [ 32] prion protein [120] ribonuclease S-peptide SARS-CoV protein [121,122] [ 36] somatostatin [123] substance P [23] T15 self-binding antibody thrombospondin-1/latency-associated peptide (LAP) TNF-a [26] [124] [125] vitronectin [93] (complementary) peptide mini-receptor inhibitors may be used to inhibit the aggregation of amyloid peptides, Ab, thereby significantly reducing Ab-mediated neurotoxicity [34]. Relatively recently, Imai et al demonstrated that HIV-1 infection can be modulated in vitro using antisense peptides that derive from internally complementary peptide sequences within the chemokine CCR5 receptor that otherwise participates with CD4 in mediating HIV-1 entry into white blood cells (leucocytes) [35].…”
Section: Extending the Applications Of Sense--antisense Peptide Intermentioning
confidence: 99%
See 1 more Smart Citation
“…(anti)-idiotypic antibodies [100,101] insulin [102] integrin [103] IFN-g [104] IFN-b [105] IL-1b IL-2 IL-18 [10,11,13,106,107] [108,109] [12] laminin receptor [110] luteinising hormone-releasing hormone [18,111] melanocyte stimulating hormone MHC II/peptide antigens [112] [113] trypsin-modulating oostatic factor [114] myelin basic protein neurokinin A/tachykinin NK1 receptor [33] [ 115] neurophysin II neutrophil chemoattractant nitric oxide synthase [77,116] [117] [118] ovine prolactin bovine P2 protein [119] [ 32] prion protein [120] ribonuclease S-peptide SARS-CoV protein [121,122] [ 36] somatostatin [123] substance P [23] T15 self-binding antibody thrombospondin-1/latency-associated peptide (LAP) TNF-a [26] [124] [125] vitronectin [93] (complementary) peptide mini-receptor inhibitors may be used to inhibit the aggregation of amyloid peptides, Ab, thereby significantly reducing Ab-mediated neurotoxicity [34]. Relatively recently, Imai et al demonstrated that HIV-1 infection can be modulated in vitro using antisense peptides that derive from internally complementary peptide sequences within the chemokine CCR5 receptor that otherwise participates with CD4 in mediating HIV-1 entry into white blood cells (leucocytes) [35].…”
Section: Extending the Applications Of Sense--antisense Peptide Intermentioning
confidence: 99%
“…Indeed, there are several pieces of evidence that are consistent with this suggestion too. For instance: 1) measured sense--antisense peptide interactions are characterised by K d values in the low µM region, so they are specific but not hugely strong [10][11][12]34,36]. Even though in biology such K d values are sufficient for certain transient interactions, binding interactions with K d values in the low nM region are routine [1]; 2) some M-I pairs remain difficult to understand because they involve amino acid residues that are hydropathic opposites, with hydrophilic residues pairing up with hydrophobic ones (Figure 4, Table 3), yet protein--protein interfaces are already known to possess substantial hydrophobic-hydrophobic amino acid residue contacts [ 3) Root-Bernstein has defined alternatives to the M-I pairs that arise by the reading of antisense codons in the 3¢ !…”
Section: Extending the M-i Pair Theory Of Interaction To The Proteomimentioning
confidence: 99%
“…Nmethylmorpholine, piperidine, dichloromethane (DCM), N,N′-dimethylformamide (DMF) and epichlorohydrin were of analytical grade and purchased from Beijing Chemical Factory, China. Monodispersed non-porous poly(glycidyl methacrylate) beads (PGMA) containing active epoxy groups were home made [11] . Triple distilled water was used throughout.…”
Section: Chemicals and Samplesmentioning
confidence: 99%
“…Moreover, Davids et al [8] developed antisense peptides as the selective inhibitors of cytokine interleukin I in 1997. Since then, antisense peptides have been designed and selected as inhibitors of cytokine interleukin-1β [9] , interleukin 18 [10] and β-amyloid peptide 1-40 [11] . In our previous work, the inhibitor of influenza A virus was designed and screened out using antisense peptide based combinatorial peptide libraries [12] .…”
mentioning
confidence: 99%
“…Antisense peptides derived from the mRNA of Aβ1-40 have also been designed to bind directly to Aβ [90]. Of the six complementary peptides synthesised, one showed specific binding to Aβ1-40 and inhibited fibrillogenesis and neurotoxicity.…”
Section: Peptide Aggregation Inhibitorsmentioning
confidence: 99%